Spark plasma sintering of molybdenum silicides synthesized from oxide precursors. Issue 10 (15th May 2021) - Ovalı, Didem; Tarraste, Marek; Kaba, Mertcan; Ağaoğulları, Duygu; Kollo, Lauri; Prashanth, K.G.; Lütfi Öveçoğlu, M.
Abstract: This work investigated the spark plasma sintering behavior of mechanochemically synthesized molybdenum silicide (MS) powders. Nanosized MS powders were obtained via a mechanochemical synthesis process applied to the initial MoO3 –SiO2 –Mg powder batches. Various characterization techniques such as X-ray diffraction (XRD), particle size analysis (PSA), Fourier-transform infrared spectroscopy (FTIR), and transmission electron microscopy (TEM) were performed to reveal the compositional and morphological properties of the homemade MS powders. The increasing sintering temperature up to 1600 °C enhanced the sinterability of the MS samples. In addition to the XRD and SEM/EDS analyses, the samples sintered at different temperatures were also characterized in terms of Archimedes' density, microhardness, and fracture toughness properties. The MS sample sintered at the temperature of 1600 °C demonstrated a relative density of 93.7%, a Vickers microhardness of 14.9 GPa, and a fracture toughness of 3.54 MPa√m. The wear rate decreased significantly with increasing sintering temperature from 3.60 × 10 −5 mm 3 /Nm (1500 °C) to 1.77 × 10 −5 mm 3 /Nm (1600 °C). Lastly, thermal gravimetry analyses (TGA) were conducted to observe the oxidation behavior of the sintered samples. The oxidation resistance of MS samples improved with increasing sintering temperatures.